2000
DOI: 10.1080/10420150008211811
|View full text |Cite
|
Sign up to set email alerts
|

Explosive decomposition of heavily irradiated NaCl

Abstract: In heavily irradiated NaCl explosions can be initiated during irradiation or later, after the irradiation, when the samples are heated to temperatures in the range 100-250°C. As a result of the irradiation Na and C12 precipitates, dislocations and voids are produced, along with stored energy (the maximum value observed until now N 76 kJ/mol, which is about 18.5% of the enthalpy of formation of NaCI, 411.2kJ/mol). This implies that heavily irradiated NaCl is a highly energetic material. We have observed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…It is important to note here that the sizes of the radiation-induced Na and Cl 2 precipitates, obtained by means of the high-resolution x-ray diffraction experiments, are much larger than those estimated from earlier investigations with other techniques [1][2][3][4][5][6][7][8][9][10][11]. In contrast with the 'x-ray sizes' in the range of several hundred angstroms, presented in tables 1 and 2, the results obtained with the other techniques suggest that the average size of the precipitates is a few dozen angstroms, which means that there is a discrepancy of at least one order of magnitude.…”
Section: Resultsmentioning
confidence: 97%
“…It is important to note here that the sizes of the radiation-induced Na and Cl 2 precipitates, obtained by means of the high-resolution x-ray diffraction experiments, are much larger than those estimated from earlier investigations with other techniques [1][2][3][4][5][6][7][8][9][10][11]. In contrast with the 'x-ray sizes' in the range of several hundred angstroms, presented in tables 1 and 2, the results obtained with the other techniques suggest that the average size of the precipitates is a few dozen angstroms, which means that there is a discrepancy of at least one order of magnitude.…”
Section: Resultsmentioning
confidence: 97%
“…1). The latter violent effects have been studied extensively during carefully executed annealing experiments [10], but we have also found strong evidence that explosion-drive fracture occurs during irradiation at very high doses. Our earlier experimental results, which have been discussed at length in [10] demonstrate very clearly that the observed explosive phenomena are driven to a large extent by instantaneous back reactions between colloidal Na and Cl 2 precipitates and cannot be explained by catastrophic cracking, which has been observed in insulators during implantation.…”
Section: Void Formation In Irradiated Naclmentioning
confidence: 88%
“…Note that real voids are not spherical [2][3][4], so the actual stresses can be higher than estimated by Eq. (13).…”
Section: Back Reaction Modelmentioning
confidence: 93%
“…Irradiation of NaCl samples generates H and F centres, which are collected together to form chlorine bubbles and sodium colloids [1]. Our experiments [2][3][4] on different NaCl samples, heavily irradiated with 0.5 MeV electrons up to fluences of 6 Â 10 18 cm À2 , have shown that with increasing irradiation dose, voids are formed followed by explosion-like fracture of the material. We explain this by a back reaction between radiolytic products.…”
Section: Introductionmentioning
confidence: 90%